2014
DOI: 10.1111/odi.12233
|View full text |Cite
|
Sign up to set email alerts
|

The 5‐year prevalence of maxillofacial fibro‐osseous lesions in Uganda

Abstract: In this study, all the florid osseous dysplasia were seen among females. We need to carry out prospective studies to establish as to why and what kind of women get afflicted by this lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
22
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 32 publications
11
22
4
3
Order By: Relevance
“…Overall, in the present study, BFOLs were slightly more prevalent in females than males. These findings that are in agreement with various similar studies [6,7,12,13]. OD is a condition that has been interpreted as a dysplastic lesion or developmental anomaly confined to the tooth-bearing areas of the jaws or to edentulous alveolar processes [14,15].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Overall, in the present study, BFOLs were slightly more prevalent in females than males. These findings that are in agreement with various similar studies [6,7,12,13]. OD is a condition that has been interpreted as a dysplastic lesion or developmental anomaly confined to the tooth-bearing areas of the jaws or to edentulous alveolar processes [14,15].…”
Section: Discussionsupporting
confidence: 92%
“…The most frequently encountered BFOLs in this study were OF and FD. This finding corresponds to reports from Nigeria [3,6] but differs from findings of a study from Uganda [7], in which FD was the most common lesion followed by OF. To the contrary, ODs were reported to be the commonest BFOLs in studies from Brazil [2] and China [1].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A recent study conducted in Uganda showed 16 new cases of FOD and called attention to the lack of information about osseous dysplasia in sub-Saharan Africa. 22 Although the disease has an evident predilection for black people, cases of FOD might be underreported or underdiagnosed in that region because of the frequent asymptomatic presentation. In general, FOD is an indolent disease discovered accidentally on routine radiography.…”
Section: Discussionmentioning
confidence: 99%